Contrasting Propagation of Natural Calls of Two Anuran Species from the South American Temperate Forest. - Mario Penna; Felipe N Moreno-Gómez (PLoS ONE, 2015)
The acoustic adaptation hypothesis predicts that sound communication signals have an optimal relationship with animals' native environments. However, species sharing a habitat produce signals stratified in the spectral domain and exhibit different temporal patterns resulting in acoustic niche partitioning. The diversity generated is likely to affect differently the characteristics of propagating signals. We recorded at various distances from the sound source calls of the frogs Eupsophus calcaratus and E. emiliopugini in the austral temperate forest where they communicate and breed syntopically. The calls of E. calcaratus have higher frequency components and lower amplitude relative to calls of E. emiliopugini, and the acoustic active space for the signals of E. calcaratus is restricted relative to E. emiliopugini. The signals of both species experience similar attenuation patterns, but calls of E. calcaratus are affected by spectral degradation to a larger extent, with linear decreases in spectral cross-correlation and in the amplitude ratio between the first two harmonics. The calls of E. emiliopugini are affected by temporal degradation as a linear decrease in amplitude modulation depth of their pulsed structure. Further studies are needed to assess the relative importance of selective and phylogenetic factors on the divergent propagation patterns reported.